The Role of Brand Ambassador, Brand Image and Brand Awareness in Shaping Purchase Decision of Calvin Klein Brand in E-Commerce Through Brand Trust as a Mediating Variable - Ferrari, Ferrari; Ahmad, Gatot Nazir; Krissanya, Nofriska (LPPPIPublishing, 2025)
This research examines the role of brand ambassadors, brand image, and brand awareness in shaping purchase decisions of Calvin Klein brand in e-commerce through brand trust as mediating variable. The research aims to explain the relationship between these variables in influencing brand trust and consumer purchase decisions. Given the rapid development of e-commerce as a primary shopping platform in Indonesia, this research is conducted to provide insights into effective marketing strategies for global fashion brands. The research employed a quantitative approach by collecting primary data through a questionnaire with 270 respondents. The analysis tool used is structural equation modelling (SEM) with SmartPLS software. The results show that brand ambassadors, brand image, and brand awareness significantly influence brand trust. Furthermore, brand trust has a direct and significant effect on purchase decisions.